Body Mass Index and COVID-19: An Overview Among an Italian Multicentric Cohort of Healthcare Workers in the Pre- and Post-Vaccination Eras—ORCHESTRA Project - Spiteri, Gianluca; Torroni, Lorena; Monaco, Maria Grazia Lourdes; Carta, Angela; Taus, Francesco; Modenese, Alberto; Casolari, Loretta; Scapellato, Maria Luisa; Liviero, Filippo; Larese Filon, Francesca; Rui, Francesca; Verlato, Giuseppe; et al. (Vaccines (Basel), 2025)
Background The prevalence of obesity is increasing all over the world, resulting in a global health emergency. The impact of obesity on the risk of SARS-CoV-2 infection and symptom severity, especially among high-risk working populations such as health workers, deserves further studies. Methods A multicentric retrospective cohort study was conducted among health workers at four Italian University Hospitals belonging to the ORCHESTRA Project. Data were collected through an online survey, investigating sociodemographic and clinical data, until September 2022. Results The questionnaire was filled out by 5777 health workers. The median age was 46 years old (I–III quartile 20–72) and 75.5% were females. Data on BMI was available for 5470 participants. Overweight and obese subjects amounted to 23.4% and 9.8%, respectively. Naïve health workers were the majority (57.4%). Overweight and obese subjects were at a higher risk of infection only before vaccination with respect to normoweight subjects (RRR = 1.28 (IC 95% 1.01–1.62, p = 0.039) and 1.36 (1.00–1.86, p = 0.047), respectively). Major acute and post-acute COVID-19 symptoms were more common among obese subjects, as compared to those with a normal weight (35.2% vs. 23.5%, and 14.2% vs. 9.3%). BMI did not reduce antibody levels after vaccination. On the contrary, overweight and obese health workers had a significantly higher RGM after the third dose (1.12 and 1.48, respectively; normal weight as reference). Conclusions Overweight and obese subjects are at a higher risk of SARS-CoV-2 infection. However, SARS-CoV-2 vaccination fosters a high antibody response even in these individuals. Vaccination against SARS-CoV-2 should be prioritized in subjects with a high BMI, especially in highly exposed workers, such as health workers.